Y. W. Ma. y Joseph S. M. Lau (cds.), Traditional Chinese Stories, Themes and Variations. New York: Columbia University Press, 1978 pp. XXXVI 603. - Maeth Ch., Russell (Estudios de Asia y África, 1981)
-